The Effect of Audit Quality, Financial Condition and Earnings Management on the Going Concern Audit Opinion with Corporate Mechanism as a Moderating Variable - Yunus Anugerah Hulu; Nagian Toni; Wilsa Road Betterment Sitepu (Облік і фінанси, 2022)
Going concern is an accounting term used to describe a business that is expected to operate for the foreseeable future or at least the next 12 months. The concept of going concern is particularly relevant in times of economic difficulties and in some situations auditor may determine that a profitable company may not be a going concern, for example because of significant cash flow difficulties. This research aims to study the influence of audit quality, financial condition and earnings management on the auditor's opinion on going concern with corporate mechanism as a moderating variable. This study analyzes data from the financial statements of 49 manufacturing companies listed on the Indonesian Stock Exchange in 2018-2020. The results of this study provide empirical evidence that giving a going concern audit opinion by the auditor is not based on the quality of the auditor because he acts in accordance with auditing standards. Financial condition and earnings management have a significant effect on the going concern audit opinion. When a company experiences a bad financial condition, it is very likely that it will receive a going concern audit opinion because there are signs of difficulties in maintaining the viability of its business. The corporate mechanism is able to moderate only the influence of financial condition on the going concern audit opinion. Thus, the auditor's opinion on going concern based on analysis of financial reporting data is important for investors and other interested parties who want to be sure of their decisions.